Pengaruh Profitabilitas, Leverage, dan Earning Pressure Terhadap Konservatisme Akuntansi dengan Kepemilikan Manajerial Sebagai Pemoderasi - Adityaputra, Stephanus Andi; Astuti, Ratna Puji (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to examine the effect of profitability, leverage, and earning pressure on accounting conservatism. The population in this study is the annually financial statements of technology sub-sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. The sample selection technique used purposive sampling. The samples that met the criteria were 26 companies with 78 observation data. The Moderated Regression Analysis (MRA) technique was used to test profitability, leverage, earning pressure on accounting conservatism and managerial ownership as a moderating variable. The results of the hypothesis test on the first hypothesis of the effect of profitability on accounting conservatism have a significance value of 0.000 < 0.05 indicating that profitability has a significant negative effect, while the second hypothesis of the effect of leverage on accounting conservatism has a significance value of 0.067 > 0.05 and the third hypothesis of the effect of earning pressure on accounting conservatism has a significance value of 0.297 > 0.05 meaning that leverage and earning pressure do not have a significant effect on accounting conservatism. Managerial ownership as a moderating variable is unable to moderate the effect of profitability, leverage, and earning pressure on accounting conservatism.